The miR-668 binding site variant rs1046322 on WFS1 is associated with obesity in Southeast Asians - Maha M. Hammad; Maha M. Hammad; Mohamed Abu-Farha; Prashantha Hebbar; Emil Anoop; Betty Chandy; Motasem Melhem; Arshad Channanath; Fahd Al-Mulla; Thangavel Alphonse Thanaraj; Jehad Abubaker (Frontiers in Endocrinology, 2023)
The Wolfram syndrome 1 gene (WFS1) is the main causative locus for Wolfram syndrome, an inherited condition characterized by childhood-onset diabetes mellitus, optic atrophy, and deafness. Global genome-wide association studies have listed at least 19 WFS1 variants that are associated with type 2 diabetes (T2D) and metabolic traits. It has been suggested that miRNA binding sites on WFS1 play a critical role in the regulation of the wolframin protein, and loss of WFS1 function may lead to the pathogenesis of diabetes. In the Hungarian population, it was observed that a 3’ UTR variant from WFS1, namely rs1046322, influenced the affinity of miR-668 to WFS1 mRNA, and showed a strong association with T2D. In this study, we genotyped a large cohort of 2067 individuals of different ethnicities residing in Kuwait for the WFS1 rs1046322 polymorphism. The cohort included 362 Southeast Asians (SEA), 1045 Arabs, and 660 South Asians (SA). Upon performing genetic association tests, we observed significant associations between the rs1046322 SNP and obesity traits in the SEA population, but not in the Arab or SA populations. The associated traits in SEA cohort were body mass index, BMI (β=1.562, P-value=0.0035, Pemp=0.0072), waist circumference, WC (β=3.163, P-value=0.0197, Pemp=0.0388) and triglyceride, TGL (β=0.224, P-value=0.0340). The association with BMI remained statistically significant even after multiple testing correction. Among the SEA individuals, carriers of the effect allele at the SNP had significantly higher BMI [mean of 27.63 (3.6) Kg/m2], WC [mean of 89.9 (8.1) cm], and TGL levels [mean of 1.672 (0.8) mmol/l] than non-carriers of the effect allele. Our findings suggest a role for WFS1 in obesity, which is a risk factor for diabetes. The study also emphasizes the significant role the ethnic background may play in determining the effect of genetic variants on susceptibility to metabolic diseases.